GA as Humanist Anthropology - Gans, Eric Lawrence (2024)
Generative Anthropology (GA) emerged from a lively intellectual universe, now largely dissipated, involving the interaction of "post-metaphysical" philosophers and miscellaneous intellectuals, mostly from literary fields, including semiologists and linguists, along with psychoanalysts and intellectual historians, that in its heyday was known under the name of French Theory. This "meta-field" was the result of a blending...